We’ve Got You Covered! The Effect of Public Health Insurance on Rural Entrepreneurship in China - Zhenggang Wang; Zenan Wu; Ye Yuan (Journal of Public Economics, 2024)
Rural households contend with numerous uninsured risks that hinder their ability to leverage profitable yet risky opportunities. We study whether the provision of insurance coverage for medical expenditure, one of the most substantial and unpredictable risk, can stimulate entrepreneurship and other risky financial decisions among rural households. We leverage the progressive nationwide rollout of a universal public health insurance program in rural China. We find that the introduction of health insurance led to a substantial increase in rural households engagement in entrepreneurship. This increase is mainly driven by the risk sharing of health insurance, rather than a reduction in realized medical expenses. The entrepreneurship-promoting effect is also evident at an aggregate level, fostering the growth of smallholder businesses in rural counties. Our findings shed light on the understudied, favorable impact of health insurance on household’s risk taking in rural markets of developing countries.